EFFECT OF FOLIAR APPLICATION OF POTASSIUM ZINC AND GIBBERELIC ACID ON YIELD AND SOME FRUIT QUALITY OF POMEGRANATE CV. SALIMY - & Ali, Jumaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The study was carried out during the growing season 2013 in a private orchard in Diyala Governorate on pomegranate trees Punica granatum L. cv. Salimy which were nine old  years, all trees that chosen had uniform in size and growth were trained on three trunks and planted at 4×4m  to study the effect of three levels of potassium sulfate  (0, 1500, 3000 mg.K.L-1) and three levels of Zinc (0, 500, and 1000 mg.Z.L-1) and three levels of Gibberellic acid (GA3) (0, 20 and 40 mg.L-1) on quality and quantity of fruit yield, A factorial experiment with three replicate was carried out according to the (RCBD) using one tree on experimental unit, the experimental results showed: Potassium achieved by concentration 3000 mg.L-1 significant decrease in the fruit cracking by 18.70%, As led to increasing in yield and some of the physical qualities of fruit as fruit yield increased, fruit weight, the proportions 41.22% and 11.48% respectively, as well as with zinc as the sprayed concentration of 1000 mg.L-1  cause a decrease of 13.86% fruits cracked, and achieved a significant increase  in  fruit yield, fruit weight, As GA3 did not have a significant effect on the qualities above, the results have shown that overlap the study showed a significant  influence factors in reducing fruits drop and cracked  and improve the physical qualities of the fruit. The results showed that the proportion of total soluble solids (TSS) were not significantly affected by three study factors and increased vitamin -C- , as a result of spraying potassium concentration 3000 mg.L-1 by 20.51% , and 8.75% at 1000 mg.L-1 of zinc, GA3 achieved  increase in  vitamin -C- by 5.66%, showed the interaction a significant effects in qualities of the above with varying proportions depending on the type of factor and its concentration  added .